Managing behavioural and psychological symptoms in community dwelling older people with dementia: 2. A systematic review of qualitative studies. (November 2019) - Braun, Andreas; Trivedi, Daksha P; Dickinson, Angela; Hamilton, Laura; Goodman, Claire; Gage, Heather; Ashaye, Kunle; Iliffe, Steve; Manthorpe, Jill
Background: People living with dementia often develop distressing behavioural and psychological symptoms (BPSD) that can affect their quality of life and the capacity of family carers and staff providing support at home. This systematic review of qualitative studies considers the views and experiences of people living with dementia and care providers about these symptoms and what helps to reduce their impact. Methods: The two-stage review involved (a) An initial mapping of the literature to understand the range of BPSD, and how it is operationalised by different groups, to develop a search strategy; (b) A search of electronic databases from January 2000 to March 2015, updated in October 2016. Included studies focused on people living in their own homes. Data extraction and thematic analysis were structured to provide a narrative synthesis of the evidence. Results: We retrieved 17, 871 records and included relevant qualitative papers (n = 58) targeting community-dwelling people with dementia and family carers around the management of BPSD. Five key themes were identified: (1) Helpful interventions/support for BPSD management, (2) Barriers to support services for BPSD management, (3) Challenges around recognition/diagnosis of BPSD, (4) Difficulties in responding to aggression and other BPSD, and (5) Impact of BPSD on family carers and people living with dementia. Conclusions: Family carers sometimes feel that their experiences of BPSD may not be evident to professionals until a crisis point is reached. Some helpful services exist but access to support, lack of knowledge and skills, and limited information are consistently identified as barriers to their uptake. The lack of common terminology to identify and monitor the range of BPSD that people with dementia living at home may experience means that closer attention should be paid to family carer accounts. Future research should include qualitative studies to evaluate the relevance of interventions.